2022
DOI: 10.1002/aic.17560
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis on anomalous phenomenon of ethanol‐soluble poly(vinyl butyral) membrane for ethanol recovery via pervaporation

Abstract: Poly(vinyl butyral) (PVB) is selected as a promising ethanol-permselective membrane based on the solubility parameter theory; however, it exhibits anomalous water perm-selectivity in practical pervaporation (PV) process. Comprehensive analysis based on experimental and theoretical methods were carried out to explore the inherent mechanism of the anomalous performance. Firstly, sum fre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…4−7 The growth in the automotive glass market is anticipated to propel the demand for laminated glass over the forecast period. Recent advancements have unveiled pioneering uses of PVB and its analogues in diverse fields, including a substrate for soft lithography, 8 a refractive layer for optical devices, 9 pervaporation membranes, 10 biodegradable packaging, 11,12 radiative cooling membranes, 13,14 and even biomedical engineering, exemplified by optical imaging, 15 skin patches, 16 and keratoprostheses. 16 The demands of these applications necessitate PVB products characterized by robust mechanical properties, strong glass adhesion, favorable solubility, and heightened thermal stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4−7 The growth in the automotive glass market is anticipated to propel the demand for laminated glass over the forecast period. Recent advancements have unveiled pioneering uses of PVB and its analogues in diverse fields, including a substrate for soft lithography, 8 a refractive layer for optical devices, 9 pervaporation membranes, 10 biodegradable packaging, 11,12 radiative cooling membranes, 13,14 and even biomedical engineering, exemplified by optical imaging, 15 skin patches, 16 and keratoprostheses. 16 The demands of these applications necessitate PVB products characterized by robust mechanical properties, strong glass adhesion, favorable solubility, and heightened thermal stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The excessive consumption of fossil fuel resources has resulted in a major global issue, known as the energy crisis. As a solution, biofuels have emerged as effective alternatives due to their renewability, high heating value, and environmental friendliness 1–6 . However, the production of bioethanol through biomass fermentation is hampered by product inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution, biofuels have emerged as effective alternatives due to their renewability, high heating value, and environmental friendliness. [1][2][3][4][5][6] However, the production of bioethanol through biomass fermentation is hampered by product inhibition. To address this issue, the in situ removal of bioethanol from fermentation broth has been proposed as an effective strategy to improve the fermentation system's productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Polydimethylsiloxane (PDMS) is a widely used polymer material for membrane fabrication, since it is easily fabricated, is chemically stable, and has a great affinity with organics as well as high hydrophobicity. The PDMS membrane can be applied for organic solvent recovery, , VOC removal, , and gas separation. , Besides, it has been reported that higher productivity and lower energy required can be achieved, if pervaporation separation by the PDMS membrane is coupled with ethanol fermentation for bioethanol in situ removal from the broth to eliminate ethanol inhibition. , In conventional methods for PDMS membrane fabrication, membrane thickness vs defects, or membrane flux vs selectivity, is always an irritating trade-off problem. Thus, optimizing the membrane thickness while limiting membrane defects to boost the separation performance is of great importance for developing PDMS membranes. In order to achieve this objective, the thin-film composite (TFC) membrane has been considered an alternative with a thinner thickness to get a higher membrane flux …”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve this objective, the thin-film composite (TFC) membrane has been considered an alternative with a thinner thickness to get a higher membrane flux. 15 In order to fabricate the TFC membrane, several approaches are developed, such as spin coating and pressure spray deposition. Compared with these approaches, electrospray is preferable to produce large, even, and defect-free membranes and is considered a more promising strategy for TFC membrane preparation.…”
Section: Introductionmentioning
confidence: 99%